Global rice market: Current outlook and future prospects - Glauber, Joseph W.; Mamun, Abdullah (International Food Policy Research Institute, 2024)
Rice is a major food crop supplying, on average, 516 kcal per capita per day or roughly 17.3% of total calories consumed globally in 2022. Rice production and consumption is concentrated in Asia though rice has grown as an important staple crop outside of Asia. Sub-Saharan Africa currently accounts for 7 percent of global rice consumption but account for over 28 percent of total rice imports. Rice is a thinly traded crop compared to other staples like wheat and maize. Rice imports account for about 10 percent of total consumption today but import penetration is expected to grow to about 11 percent by 2033. India is the world’s largest exporter accounting for about 40 percent of total exports in recent years. Pakistan, Thailand, Vietnam and the United States account for an additional 40 percent of world exports. Mid-range projections for the next 10 years suggest that trends in place will likely continue. Yields are assumed to keep pace with global consumption trends. Sub-Saharan Africa will account for a significant share of the overall growth in consumption. The US Department of Agriculture (USDA) forecasts that Sub-Saharan Africa will account for 27 percent of the growth in global rice consumption and 47 percent of the growth in global imports over the next 10 years. Climate and government distortions remain the single largest vulnerabilities to the rice market. Because of the large concentration of rice production in South and Southeast Asia, crop production is vulnerable to El Niño and other climatic events like the Indian Ocean Dipole which can bring hot and dry weather and disrupt the monsoon season. Since rice is so thinly traded, market restrictions imposed by one of more of the major exporting countries can cause large price impacts. In 2007/08, export bans affected as much as 80 percent of rice trade which caused global prices to almost triple. In July 2023, India imposed export restrictions fearing that domestic production would be harmed by a developing El Nino event. Global rice prices rose by 30 percent as a result. Importing countries bore much of the brunt of those increases, particularly poorer countries in the rice-importing areas of Sub-Saharan Africa. Other potential vulnerabilities include logistical issues, particularly bottlenecks in the major shipping lanes of Asia.